2011
DOI: 10.1002/ccd.23232
|View full text |Cite
|
Sign up to set email alerts
|

Transfemoral use of the guideLiner catheter in complex coronary and bypass graft interventions

Abstract: The GuideLiner catheter (Vascular Solutions, Minneapolis, MN) is a novel, rapid exchange catheter that allows deep vessel intubation. We describe 21 patients in whom the GuideLiner catheter [7 French (F) in 76% and 6F in 24%] was used to facilitate equipment delivery (n = 14) or vessel engagement (n = 7). Pressure dampening after GuideLiner catheter insertion was observed in 12 patients (57%). The procedure was successfully completed in 19 patients (90%) and one patient developed acute vessel closure, likely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 37 publications
3
36
1
Order By: Relevance
“…[6][7][8][9] . The GuideLiner (GL) catheter (Figure 1) is a novel rapid exchange guide catheter extension system that provides active guide support by its 20 cm-long flexible tubular end, which can be deeply advanced into target vessels [10][11][12][13][14][15][16][17][18] . Its handling is particularly easy, as it is does not require disconnection of the haemostatic valve at the proximal end of the guide catheter and is compatible with standard 180 cm-long guidewires.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9] . The GuideLiner (GL) catheter (Figure 1) is a novel rapid exchange guide catheter extension system that provides active guide support by its 20 cm-long flexible tubular end, which can be deeply advanced into target vessels [10][11][12][13][14][15][16][17][18] . Its handling is particularly easy, as it is does not require disconnection of the haemostatic valve at the proximal end of the guide catheter and is compatible with standard 180 cm-long guidewires.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only a limited number of reports and case series have been published on the GL guide catheter extension [10][11][12][13][14][15][16][17][18] . Mamas et al reported a case series of 13 complex coronary interventions, performed via the radial artery with the "5-in-6" Fr GL system 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luna et al 6 reported dissection in the proximal anterior left descending artery during intubation with a GuideLiner TM 7 F. Murphy and Spence 7 described their first complication with the use of the GuideLiner TM during primary coronary angioplasty of the ostium of the right coronary artery while withdrawing of the GuideLiner TM over the stent for its release: a perforation of the balloon catheter system occurred, caused by the metal collar and the incapacity to appropriately inflate the stent balloon.…”
Section: A D E F B Cmentioning
confidence: 99%
“…Guide catheter extensions carry a cost, which may, however, be offset by savings in additional equipment that would have been required to facilitate the procedure. They also carry a risk of complications: deep engagement can lead to vessel dissection (4, 6, 12), and advancing equipment through the extension may result in deformation or equipment loss (13, 14). Moreover, it is important to know what can and what cannot pass through a guide catheter extension, since it effectively decreases the inner guide lumen by approximately 2 French.…”
mentioning
confidence: 99%